Visual Storytelling: A Contemporary Approach to Online Journalism for the Millennial Generation - Ardilla, Yunda Presti; Aini, Devi Nur; Kusuma, Bima Aditya; P.H., Aurelia Lintang (VCD: Journal of Visual Communication Design, 2024)
This case study examines the topic of digital visual content, information dissemination, art, and culture for local Indonesian products on the Instagram account Folkative. Folkative is a company targeting a young audience, primarily millennials. Founded to inspire, inform, and represent the diverse creative culture of Indonesian youth, Folkative accomplishes this through the creation of content and interactive online events aimed at the youth of today. The communication style of the Folkative Instagram account has a significant impact on online activities and the evolution of millennial communication patterns. This research employs a qualitative approach using the case study method. The researcher conducted in-depth interviews with 5 informants selected through purposive sampling criteria. The results of this study indicate that the form of content, quality perception, and reader attitudes support the dissemination of content through the Instagram account Folkative. Visual design, which presents the power of images, has become a suitable medium for storytelling, and it is favored by the millennial generation, particularly in the context of journalism. This transformation has shifted the style of journalism from traditional audio and text-based formats to visual art that narrates current and meaningful information for the audience, thus enhancing the literacy interests of the digital native generation.